2017
DOI: 10.1007/s10368-017-0390-6
|View full text |Cite
|
Sign up to set email alerts
|

Saving and investment causality: implications for financial integration in transition countries of Eastern Europe

Abstract: Numerous studies have been devoted to the Feldstein-Horioka puzzle. However, no consensus has been reached in the literature. This paper examines the causal relationship between domestic saving and investment rates in six transition economies (Estonia, Latvia, Lithuania, Ukraine, Belarus, and Russian Federation). Theoretically, the presence of any type of causal structure between these two series in a country implies that national capital markets are not open; hence capital flows are impeded. Therefore, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…nations over the period 1971-2002, and Ketenci [10] for Estonia and Portugal between 1995-2009. The findings of causality from savings to investments in the study are in line with that of Esso and Keho [5], and Irandoust [8] that reported unidirectional causality from savings to investment, indicating, savings spur domestic investment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…nations over the period 1971-2002, and Ketenci [10] for Estonia and Portugal between 1995-2009. The findings of causality from savings to investments in the study are in line with that of Esso and Keho [5], and Irandoust [8] that reported unidirectional causality from savings to investment, indicating, savings spur domestic investment.…”
Section: Discussionsupporting
confidence: 90%
“…Al-Afeef and Ali Al-Qudah [1] investigated the savings-investment link for Jordan economy for the period 1980 to 2013 using the Johansen cointegration method and reported a significant long-run association between savings and investment and concluded that there is perfect capital mobility international in Jordan. Irandoust [8] assessed the direction of causality between savings and investment for six transition countries using the bootstrap panel causality test to verify whether capital is fixed internationally or mobile. The study findings indicate significant causality between savings and investment in the countries reviewed, indicating capital immobility internationally.…”
Section: The Experimental Check Of the Relationship Between Savings Amentioning
confidence: 99%
“…But the research outcomes are mixed in explaining this hypothesis. Several studies concluded the existence of a high degree of savingsinvestment association and thus, low level of international capital mobility thereby supporting F-H hypothesis in large and small economies (Akkoyunlu, 2020;Lam, 2012;Bagheri & Hazrati, 2012;Eyuboglu & Uzar, 2020;Hassan et al, 2014;Irandoust, 2019;Petreska & Mojsoska-Blazevski, 2013;Tasar, 2017;Yildirim & Orman, 2018). Nevertheless, this correlation was found to be weaker for developing economies (Adeniyi & Egwaikhide, 2013;Bangaké & Eggoh, 2010;Chan et al, 2011;Chang & Smith, 2014;Coakley et al, 1999;De Wet & Van Eyden, 2005;Dooley et al, 1987;Horioka et al, 2015;Kasuga, 2004;Mamingi, 1997;Mumtaz & Munir, 2016;Patra & Mohanty, 2020;Payne & Kumazawa, 2005;Raheem, 2017;Shahbaz et al, 2010;Sinha & Sinha, 2004;Vamvakidis & Waczairg, 1998;Wong, 1990;Younas, 2007).…”
Section: Literature Reviewmentioning
confidence: 92%
“…A number of papers have tried to address causality between savings and investment rates using Granger-causality tests in panel settings (for example Attanasio, Picci, and Scorcu, 2000;Irandoust, 2019). The evidence generally suggests that the null hypothesis that savings Granger -cause investment typically cannot be rejected.…”
Section: Assessing Causality With Instrumental Variablesmentioning
confidence: 99%
“…Recent contributions have used panel co-integration methods and granger causality tests focusing on certain groups of countries to re-examine the relationship between domestic savings and investment (Cavallo and Pedemonte, 2015;Irandoust, 2019). Dooley, Frankel and Mathieson (1987) is the only paper we are aware of that uses an IV approach.…”
Section: Introductionmentioning
confidence: 99%